Valoração econômica dos recursos naturais e ambientais: um estudo de caso do Parque das Dunas, Natal/RN - Barros, André Luís Firmino de Brito (2013)
The economic valuation of environmental assets has gained relevance as instruments to assist the decision making of managers both public and legislators, as investors and entrepreneurs. Assign an economic value to environmental resources is not yet a widespread practice. The environmental management has been focused mainly on assessment of the impacts generated by the unbalanced exploitation of these resources. Therefore, this work has as overall goal performing economic valuation of Dunes State Park of Natal in Natal/RN, analyzing the Willingness to Pay (WTP) for students and employees of the Federal Institute of Education, Science and Technology of Rio Grande do Norte (IFRN) through Contingent Valuation Method (CVM), considering its natural attractions, and specific objectives, we analyze the socioeconomic profile of students and employees and their concerns about environmental issues, as well we estimate the function WTP for the use of environmental attractions of the park. Finally, we relate the value of the WTP Park socioeconomic characteristics of the students and IFRN servers. As methodology, we used a bibliographic review of the existing literature and a field research, executed at Federal Institute of Education, Science and Technology of Rio Grande do Norte (IFRN), Natal-campus center, where we applied a questionnaire in the open form of elicitation, during September of 2012, among students aged 18 years and servers (administrative staff and teachers) of this educational institution, gathering also socioeconomic information of the individuals. The results demonstrated that through the regression model, analyzed in general, we have evidence for a significance level of 6,8% there is a significant difference between the amount willing to pay for the maintenance of the park with family income and net income, in other words, as the individual has a higher net income and family, value willing to pay for the maintenance of the Dunes state Park tends to be higher. Furthermore, it was detected that there is also significant effect with respect to schooling, where as you increase the educational level of the individual, the average willing to pay for the maintenance of the Dunes state Park also increases. A fact relevant as adjustments in the general model, it is found not to have significant effect on the amount willing to pay for the maintenance of the Dunes state Park with respect to students and servers.